MANAJEMEN KONSERVASI PADA WISATA PURA GOA GAJAH - Giri, Kadek Risna Puspita (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Bali is a place rich of history and has preserved many archaeological sites, such as“Pura Goa Gajah” site in gianyar Regency. This archaeological site has a very big potential to attract domestic and foreign tourist.However, as the time progresses, Pura Goa Gajah showsdamage which needs special attention through the conservation process, to prevent the site from extinction. Based on this background, this research try to formulate problem about the environmental impact on vulnerability of “Pura Goa Gajah” site, collect data of damage process happened and their influence factor. The purpose of this research is to evaluate the current damage, so conservation plans can be made to prevent further damage by using 5 M+ (Man, Money, Method, Machine, Material)+Marketing concept. This is done in order to help conservation efforts for“Pura Goa Gajah”site and suit the principle of conservation, which is sustainable.